2012
DOI: 10.2147/ijn.s29376
|View full text |Cite
|
Sign up to set email alerts
|

Improving thermal stability and efficacy of BCNU in treating glioma cells using PAA-functionalized graphene oxide

Abstract: Background: 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU), a commercial chemotherapeutic drug for treating malignant brain tumors, has poor thermal stability and a short half-life. Immobilization of BCNU on a nanocarrier might increase the thermal stability of BCNU and extend its half-life. Methods: Nanosized graphene oxide (GO) could be modified by polyacrylic acid (PAA) to improve the aqueous solubility and increase the cell penetration efficacy of the nanocarrier. PAA-GO intended as a drug carrier for BCNU wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Other cancer types such as Burkitt's lymphoma 33 , colon cancer 34 , 70 , 71 , 78 , 91 , prostate cancer 35 , 64 , 87 , lung cancer 43 , 56 , 63 , 76 , 80 , 87 , skin cancer 57 , 60 , brain cancer 20 , 38 , 46 - 48 , 61 , 62 , glioma 90 and glioblastoma 72 were studied under different drug treatment conjugated with graphene or graphene oxide.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Other cancer types such as Burkitt's lymphoma 33 , colon cancer 34 , 70 , 71 , 78 , 91 , prostate cancer 35 , 64 , 87 , lung cancer 43 , 56 , 63 , 76 , 80 , 87 , skin cancer 57 , 60 , brain cancer 20 , 38 , 46 - 48 , 61 , 62 , glioma 90 and glioblastoma 72 were studied under different drug treatment conjugated with graphene or graphene oxide.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…GO-PVA-CPT exhibited higher cytotoxic activity versus cancer cells compared to CPT alone. A lot of drugs were used in multiple conjugations with graphene such as camptothecin 32 , 66 , 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) 38 , a commercial chemotherapeutic drug for treating malignant brain tumors, tamoxifen citrate 43 , elsinochrome A 44 , adriamycin 40 , β-lapachone 41 , lucanthone 72 , paclitaxel 56 , 76 , anastrozole 65 , 5-fluorouracil 55 , epirubicin 48 , 62 , curcumin 68 , gambogic acid 86 ellagic acid 34 , oxaliplatin (OXA) 91 , cisplatin 91 and thermosensitive nanogel 64 . All these studies showed a great improvement in therapeutic efficacy when the drugs were loaded onto graphene.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…For example, chemotherapeutic drugs possessing aromatic ring structures, such as doxorubicin, camptothecin, and SN-38, bind on GO through π–π stacking. 47 Various methods have been developed to functionalize GO for improving its drug carrier function. Lui et al found that GO functionalized with polyethylene glycol (PEG) can carry water-insoluble cancer drugs such as camptothecin and SN38 and showed pH-dependent drug release behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The PAA–GO–BCNU showed promising anticancer efficacy in in vitro study. 47 Yin et al functionalized GO with PEI and (PEG) as a plasmid-based Stat3 siRNA carrier, which showed a significant regression in tumor growth and tumor weight of mouse malignant melanoma growth in vivo. 50 Yang et al developed epidermal growth factor receptor (EGFR) antibody-conjugated PEGylated nanographene oxide (PEG-NGO) carrying epirubicin (EPI) that was able to target the tumor and kill the cancer cells by its triple-therapeutics (growth signal blocking, chemotherapy, photothermal therapy).…”
Section: Discussionmentioning
confidence: 99%
“…Already in 2012 Chen et al had incorporated a chemotherapeutic agent, belonging to the nitrosourea family, into a molecule of oxidized graphene conjugated with polyacrylic acid (1,3-bis(2-chloroethyl)-1-nitrosourea). In vitro studies on GL261 glioma cells demonstrated the drug uptake via endocytosis and the greater efficacy of the drug conjugate compared to the virgin drug [49].…”
Section: Carbon Nanomaterials and Brain Tumorsmentioning
confidence: 99%